3d Printing-Assisted Fabrication of Microfluidic Pneumatic Valves - Keleş, Şeyda; Tekin, Hüseyin Cumhur; Karakuzu, Betül; Tekin, Hüseyin Cumhur (IEEE, 2023)
Pneumatic valves have a crucial place in the fluidic control in microfluidic systems. Pneumatic valves containing polydimethylsiloxane (PDMS) membrane structures are used in microfluidic systems such as cell separation, and cell manipulation due to their flexible structure, and ease of production. This study demonstrates the rapid and straightforward fabrication of pneumatic valve structures using PDMS membranes, achieved through the utilization of 3D-printed molds. As a result of our experiments, we observed valve closure in a fluidic channel with a height of 150 μm. This closure was achieved by utilizing 400 μm × 800 μm PDMS membrane with a thickness of 66 μm positioned between the fluidic and control channels, while applying 1.5 bar of pressure to the control channel. When the pressure is removed, the opening time of the valve is only 0.02 s, and this response time allows rapid valving function. The presented valve fabrication strategy would allow easy and low-cost production of sophisticated microfluidic chips. © 2023 IEEE.
2023 Medical Technologies Congress, TIPTEKNO 2023 -- 10 November 2023 through 12 November 2023
Keywords: Flow control; Microfluidics; PDMS membrane; Pneumatic valve